KEKUATAN ALAT BUKTI MESIN POLYGRAPH DALAM PERSIDANGAN PERKARA PIDANA DI INDONESIA - Ruspian, Ruspian; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In a state of law, the function of law is not only as a means of social control or a means of maintaining stability . In criminal cases, proof has an important role in determining someone suspected of being guilty of committing a crime, the community involved in the judicial process. The proof system adopted by the Criminal Procedure Code (KUHAP) is a system of proof according to the law in a negative way ( Negatief wetelijk stelsel ). The negative verification system is strengthened by the principle of freedom of judicial power . Article 184 paragraph (1) of Law Number 8 of 1981 concerning the Criminal Procedure Code states that the evidence is valid one of them is evidence evidence. One of them is the use of a polygr A ph machine or a lie detector. Machine polygr a pH is one means of evidence in the investigation process that is currently used in the process of examination of evidence in Indonesia.The purpose of writing this thesis, namely; First, To menge tahui setting machine Polygraph as a means of proof in pembuk tian court cases criminal , secondly, to menge tahui Strength Tool Proof Machine Polygraph in Proof Trial Case Crime in Indonesia. The writing of this thesis uses a juridical normative approach method with research specifications by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. With this method the authors analyze the problems based on legal principles, legal concepts and norms, the legal angle based on existing laws and regulations , and legal theories relating to facts relevant to legal issues.Based on the results of the study, it can be concluded that the results of the polygraph machine are legally used in criminal justice processes in Indonesia, the arrangements of which are listed in article 184 of the Criminal Code by adopting a negative proof system as evidence of instructions and supported by Law Number 19 of 2016, amendments to the Law Law Number 11 Year 2008 concerning Information and Electronic Transactions. supported by Order Number Pol: Sprin / 295 / II / 1993 concerning the Validation of the Indonesian National Police Organization, namely about the Police Forensic Laboratory . Authors' suggestion, There needs to be additional regulations so that the position of this evidence is clear. And in proving the judge must first look at the procedure for using this lie detector tool whether there is an element of physical pressure on the suspect or not because it will affect the results of the lie detector itself.Keywords: evidence evidence instructions - polygraph - proof